(untitled) (Hungarian Journal of Industry and Chemistry, 2009)
The main objective of this study is to provide a general mathematical model in a compact form for batch diafiltration techniques. The presented mathematical framework gives a rich representation of diafiltration processes due to the employment of concentration-dependent solute rejections. It unifies the existing models for constant-volume dilution mode, variable-volume dilution mode, and concentration mode operations. The use of such a mathematical framework allows the optimization of the overall diafiltration process. The provided methodology is particularly applicable for decision makers to choose an appropriate diafiltration technique for the given separation design problem.